PENGARUH REMUNERASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI RSUP Dr. M. DJAMIL PADANG DI RUANG LINGKUP DIREKTORAT KEUANGAN - Liza Zulbahri; Nurlina Nurlina (Ensiklopedia of Journal, 2021)
The purpose of this study was to determine and analyze the effect of remuneration and organizational commitment partially and simultaneously on the performance of the employees of RSUP Dr. M. Djamil Padang In the Scope of the Directorate of Finance. The research method used is descriptive quantitative. The sampling technique used was total sampling so that the entire population was used as a sample in this study as many as 74 nurses, the data collection methods used were observation, interviews, questionnaires and library reviews. The data analysis technique used is multiple linear regression, t test, F test and coefficient of determination. Based on the results of the t test, it is known that remuneration (X1) has a positive and significant effect on employee performance with a significant value of 0.042 <0.05 and the value of tcount (2.066) > ttable (1.666) organizational commitment (X2) has a positive and significant effect on employee performance with significant value 0.000 <0.05 and tcount (6.115) > ttable (1.666). Based on the results of the F test, it is known that the remuneration variable (X1) and organizational commitment (X2) have a positive and significant effect on employee performance together with a value of Fcount (26.029) > Ftable (3.13) and a significant value of 0.000 <0.05. While the results of the coefficient of determination test obtained an Adjusted R-Square value of 0.407. This means that the ability of the remuneration variable (X1) and organizational commitment (X2) in explaining employee performance variables is 40.7% while the remaining 49.3% is explained by other variables not discussed in this study.